Whistleblowing as an anti-corruption strategy in health and pharmaceutical organizations in low- and middle-income countries: a scoping review. Issue 1 (31st December 2022) - Vian, Taryn; Agnew, Brianna; McInnes, Keith
ABSTRACT: Background: Whistleblowing can bring suspected wrongdoing to the attention of someone who is in the position to rectify the problem. Whistleblowing research can help improve effectiveness of anti-corruption efforts in the health sector. Objective: The objective of this scoping review is to understand the extent and type of evidence on whistleblowing as an anti-corruption strategy in health and pharmaceutical organisations in low- and middle-income countries (LMICs). Methods: This scoping review searched the PubMed, Scopus, and EMBASE databases from 2005 to 2020, limited to English language. We also searched websites of multilateral agencies or international non-governmental organisations for policy documents, guidance and reports. Titles and abstracts were screened to remove those where the focus was not on health, pharmaceuticals, whistleblowing, or LMIC context. Articles focused on research misconduct were excluded. Full-text articles were assessed for eligibility on these same criteria. Included sources were analysed thematically, based on five categories including definitions and models; evidence of reporting frequency; factors influencing whistleblowing; cultural context; and outcomes. Results: The review found 22 sources including reports, policies, and guidance documents (12, 55%), news articles (4, 18%), policy analyses/reviews (3, 14%), commentaries (2, 9%), and empirical studies (1, 5%). Most sources described whistleblowing policy and system components such as how whistleblowing is defined, who can report, and how confidentiality is assured. Few articles documented types and frequencies of corruption identified through whistleblowing or factors associated with whistleblowing. Several studies mentioned cultural norms as a potential limitation to whistleblowing effectiveness. About one-third of the sources described fear of retaliation and noted the need to strengthen protection for whistleblowers. Conclusion: Research on whistleblowing is scarce in health and pharmaceutical organisations in LMICs. Documentation of policies, factors associated with whistleblowing, and whistleblowing outcomes is needed and could help countries to mainstream whistleblowing as a sectoral anti-corruption strategy.